Oxford dictionary of English idioms - Cowie, A P; Mackin, R; McCaig, I R (Oxford Oxford University Press, 1998)
A comprehensive dictionary dealing with general idiomatic expressions in current English.
Keywords: Ngôn ngữ Anh